Water-loaded metal diagonal horn applicator for hyperthermia - Singh S.; Singh S.P. (My University, 2025)
This study presents the design of water-loaded metal diagonal horn antenna at 2450 MHz along with simulation and experimental studies of specific absorption rate (SAR) and temperature distributions in a bio-medium (muscle) in direct contact with the water-loaded antenna for hyperthermia application. The metal diagonal horn is a multimode horn antenna, with identical aperture field distribution in the E- and H-planes. The SAR distribution in a phantom muscle in direct contact with water-loaded horn antenna measured at 2450 MHz is nearly in agreement with the corresponding simulated distribution. The simulation results for SAR distribution owing to diagonal horn are also compared with those owing to square aperture horn/box horn, of same aperture cross-section/broader dimension as the diagonal horn at 2450 MHz. The results indicate that the diagonal horn provides higher penetration depth/better transverse resolution over square aperture horn/box horn. In addition, the proposed diagonal horn provides circularly symmetric effective field size. Finally, thermal simulation results are also provided for the proposed applicator, which is in direct contact with a realistic model of muscle medium without and with small spherical as well as oval-shaped tumours of different dielectric properties embedded within the muscle medium. © The Institution of Engineering and Technology 2015.